Acetobacter sp. improves the undesirable odors of fermented noni (Morinda citrifolia L.) juice. (1st February 2023) - Zhang, Lin; Hong, Qiongping; Yu, Chengfeng; Wang, Ruimin; Li, Congfa; Liu, Sixin
Highlights: The flavor profiles of fermented noni juice inoculated with Acetobacter sp. were analyzed by GC-IMS. 14 differential biomarkers were screened by OPLS-DA. Hexanoic acid, octanoic acid and butanoic acid were major unpleasant ingredients. Hexanoic acid, octanoic acid and butanoic acid were significantly decreased or even eliminated in the fermentation process. The fermentation was basically completed on the 6th day after inoculation with Acetobacter sp. Abstract: To clarify the role of Acetobacter sp. in fermented noni juice, the physiochemical properties, main active ingredients and volatile constituents were comprehensively analyzed. The sugar content and acidity tended to be stable after 12 days of fermentation. Acetobacter sp. had no significant influence on major active ingredients of products. The headspace-gas chromatography-ion mobility spectrometry (HS-GC-IMS) were performed to describe the characteristic flavor profiles during fermentation. A total of 55 flavor compounds were screened with odour threshold and Kruskal-Wallis p  < 0.05. Among them, 14 different biomarkers were selected with Variable Importance in Projection ( VIP)  greater than 1. The concentrations of ketones and aldehydes increased significantly, mainly contributing to the floral, fruit and green features. The content of hexanoic acid, octanoic acid and butanoic acid as the main source of peculiar odor were significantly reduced, indicating Acetobacter sp. could improve the unpleasant odor of fermented noni juice.